Immunodeficiency risk score for prediction of mortality by parainfluenza virus infection in patients with hematologic malignancy - Lee, Jeongsoo (Ann Hematol, 2020)
Parainfluenza virus (PIV) infection is a significant cause of morbidity and mortality, especially in hematologic malignancy patients including hematopoietic stem cell transplantation (HCT) recipients. However, limited information is available for risk stratification in PIV-infected patients with hematologic malignancy with or without HCT. Patients with hematologic malignancy diagnosed with PIV from January 2009 to December 2018 were retrospectively included in a tertiary care hospital in Seoul, South Korea. Upper respiratory tract infection (URTI) was defined as the detection of PIV in a nasopharyngeal sample with URTI symptoms without new pulmonary infiltrates. Lower respiratory tract infection (LRTI) was defined as detection of PIV in either upper or lower respiratory tract samples with new pulmonary infiltrates, with or without hypoxia. PIV-associated mortality was defined as death with respiratory failure and persistent LRTI within 90 days after diagnosis. The study included 143 adult patients. Of these, 55 (38%) progressed to or initially presented with LRTI. Among these, 22 (40%) died from PIV-associated mortality. An immunodeficiency risk score was developed from associated risk factors using a multivariable Cox regression model. Patients were stratified into low (0–2), moderate (3–5), and high risk (6–8) groups with PIV-associated mortalities of 0%, 9%, and 67%, respectively (p < 0.005, Harrell’s C-index = 0.84). PIV infection can result in substantial mortality in patients with hematologic malignancy if it progresses to LRTI. The immunodeficiency risk score presented here may be useful for distinguishing moderate and high risk groups that might benefit from antiviral therapy.